Enhancing Regional STEM Teacher Development: Strategies and Insights from Professional Learning Facilitators in Afghanistan - Sayedy Javad; Abdullah Qutuby; Bakhshi Naseem (Advances Educational Innovation, 2024)
Objective: The purpose of this study was to gain insights into how Professional Learning Facilitators PLFs promoted STEM teacher learning in Afghanistan’s regional context. It aims at uncovering best practices of the facilitators and its teacher educators to inform sustainable professional development approaches seeking to address the specific reality of the Afghan context.Methods: A mixed-methods approach was employed, consisting of qualitative interviews with PLFs and a survey of STEM teachers in some regional areas of Afghanistan. Descriptive statistics and thematic analysis were used to analyze data and identify trends and common strategies to enhance teacher learning.Results: Responding to challenges arising from the regional context, PLFs in Afghanistan work through a combination of hands-on workshops, collaborative learning environments, and context-sensitive content. These approaches have increased engagement among teachers and enhanced instructional practices despite differing impacts due to geography and resources.Novelty: It fills a unique gap in the literature on education development in post-conflict regions, as we shed light on STEM teacher professional development within the unique socio-political context of Afghanistan.Theory and Policy Implications: The study can inform the development of change frameworks for professional learning that can be used to ensure professional learning is responsive to the context and the community in which it is situated. It highlights the importance of policies that promote sustained long-term teacher development in contexts affected by conflict should aim to design strategies to develop scale and relevance to context.